(3QhVI GdMaGX HJgPjH GdCdaGXs - (3ehSi Hf GdMSjf GdebQFs ((3YHO GdYRjR Hf aJhM Hf efUhQ s)
(3ChdgG (B:s
(3jHOC HHGH PcQ GdjGAGJ GdeVGaGJ hGdeMPhaGJ hENJdGb GdYGOjf ai Ci GdShQ aGJMI GdcJGH s
(3BNQgG (B:s
(3abGd SCdJ LHQjd ceG SCdJfi abGdJ SCdJ ESQGajd ceG SGdfi abGd di gcPG hLOJg ai GddhM Yf Gdbde Yf QH GdYGdejf BNQ cJGH QhVI GdMaGX hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HBNQg SeGYGJ hbQGAGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdbQGAGJ hGdJLhjOs